Privacy concerns surrounding personal information sharing on health and fitness mobile apps - Sen, Devjani, 1970-; Ahmed, Rukhsana (Advances in information security, privacy, and ethics (AISPE) book series., 2021)
"This book provides research on the dangers of sharing personal information on health and wellness apps, as well as how such information can be used by employers, insurance companies, advertisers, and other third parties"--